Coexistence of Ankylosing Spondylitis and Klinefelter's Syndrome - Şenol Kobak; Murat Yalçin; Muamer Karadeniz; Guray Oncel (Case Reports in Rheumatology)
Ankylosing spondylitis is a chronic inflammatory disease characterized by inflammatory lower back pain and morning stiffness and accompanied by spine and sacroiliac joint involvement. Klinefelter's syndrome is a genetic condition that only affects males. Affected males have an extra X chromosome. This paper reports a 30-years-old male on followup with the diagnosis of Klinefelters syndrome. The patient admitted with complaints of inflammatory lower back, and neck pain and morning stiffness and was diagnosed with ankylosing spondylitis. Nonsteroidal anti-inflammatory drug and salazopyrine treatment resulted in significant regression in his complaints.